Failure of silicon nitride ceramic flotation spheres at critical state of implosion. (April 2020) - Zhang, Xiaolong; Feng, Miaolin; Zhao, Min; Zhang, Peizhi; He, Chenggui; Qi, Hai; Han, Weiyue; Guo, Fangquan
Abstract: Silicon nitride ceramic flotation spheres have great potential for use in deep-sea exploration vehicles because they can efficiently provide buoyancy. However, the material characteristics of ceramic and the high-pressure service environment in the deep sea mean that the spheres have a large risk of implosion, which has devastating consequences for the spheres and their surroundings. This study focuses on the failure of hollow silicon nitride ceramic flotation spheres at the critical state of underwater implosion with finite element analysis. First, the implosion experiments of silicon nitride flotation spheres under large hydro-static pressure was examined. Next, the first-order buckling mode for the structure was introduced into the explicit dynamic analysis as the initial geometric imperfection, and the failure process of the flotation sphere with eigenmode geometrical imperfections was obtained. Then a real silicon nitride ceramic flotation sphere geometry, obtained by computed tomographic scanning, was imported into the finite element simulation. Finally, the effect of sphericity on the implosion results was investigated, and the results show that a perfect hollow sphere has the best pressure resistance. The simulations indicate that failure begins from the internal surface, and preload compression treatment of the inner surface might enable better performance by ceramic flotation spheres.